2008
DOI: 10.2514/1.32559
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Gravitational Force Representation for Fast Trajectory Propagation Near Small Bodies

Abstract: We present an approximation scheme for gravitational forces near arbitrarily shaped small bodies. The approximation uses polynomial interpolation with an adaptive spatial data structure near the asteroid and spherical harmonics far from it. These data structures allow us to drive the approximation errors of the model to within userdefined thresholds, while significantly reducing the run time of trajectory integrations about small bodies. This alleviates the computational burden of Monte Carlo simulation for sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 16 publications
0
27
0
Order By: Relevance
“…Its gravitational field near the asteroid could hardly be denoted by using the spherical harmonics expansion because it is only valid outside a circumscribing sphere. Assuming that the density of the asteroid is uniform, the accurate potential function of the polyhedral asteroid can be computed by the method reported in [11][12][13]. However, this method is relatively time consuming, especially when it is used in the numerical integration, and it is very difficult to use in the nonuniform density case.…”
Section: A Polyhedral Shape Model Of Irregular Asteroidsmentioning
confidence: 99%
“…Its gravitational field near the asteroid could hardly be denoted by using the spherical harmonics expansion because it is only valid outside a circumscribing sphere. Assuming that the density of the asteroid is uniform, the accurate potential function of the polyhedral asteroid can be computed by the method reported in [11][12][13]. However, this method is relatively time consuming, especially when it is used in the numerical integration, and it is very difficult to use in the nonuniform density case.…”
Section: A Polyhedral Shape Model Of Irregular Asteroidsmentioning
confidence: 99%
“…Exactness: All conservative forces are the gradient of some potential field. The cubetree method presented in [6] does not respect this qualitative feature. This is especially important for long-term simulation where qualitative features of the trajectories are of primary interest.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a novel numerical scheme (the cubetree algorithm) for the fast evaluation of gravitational force around irregular bodies has been introduced by the authors [6] and shown to provide a significant speed improvement over other methods. The scheme exploits the availability of large storage capacities to reduce the online computations.…”
Section: Introductionmentioning
confidence: 99%
“…Interpolation models have been developed to make evaluation faster. Some of these models preserve the spherical coordinate system [3,4], while others drastically reformulate the evaluation of the gravity field [5,6].…”
Section: Introductionmentioning
confidence: 99%